Scientific research in quinoa and its relationship with the economic return between the years 1999 to 2020 (Agroindustrial Science, 2022)
The public funds of the countries are scarce, especially in developing countries, with the government making decisions in the allocation of resources for agricultural research. The objective was to determine the economic return of investment in scientific research on the productivity of quinoa (Chenopodium quinoa Willd) in Peru from 1999 to 2020. For this, data from the United Nations Food and Agriculture Organization was used. (FAO) and the Ministry of Economy and Finance of Peru; the research is non-experimental and basic. Likewise, linear regression was used for data analysis and an increase in production was found from 1978 (529 kg/ha) to 2020 (1480 kg/ha), the Internal Rate of Return (IRR) is 16.1% and the Benefit/Cost ratio is on average 1.42; Therefore, investment in research has high economic returns and great benefits for society.
Keywords: Quinoa; research; innovation; economic returns